The effect of ceramic vases on the acoustics of old Greek orthodox churches - Zakinthinos, Tilemachos; Skarlatos, Dimitrios (My University, 2007)
The effect of resonators on the acoustics of orthodox churches was studied. Empty bottles of commercial refreshment were used as resonators. A total number of 480 resonators having the same resonant frequency, were placed inside a church, in steps of 100 resonators each time, and the impulse response of the church was measured and analyzed in 1/1 and 1/3 octave band analysis. The effect of resonators is rather poor. An amplification of sound in the near field of resonators was observed as well as a small attenuation of the sound level in the reverberant part of the field in the resonant frequency and near to a higher overtone. A remarkable increase of C80 and D50 at resonant frequency was also observed.
Keywords: Church acoustics; Pots; Clarity; Definition